2022
DOI: 10.1002/fsn3.3123
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acorn muffin consumption on glycemic indices and lipid profile in type 2 diabetic patients: A randomized double‐blind placebo‐controlled clinical trial

Abstract: Despite the presence of various approaches for controlling diabetes mellitus (DM), such as dietary adjustment (Asif, 2014) and hypoglycemic agents, some patients do not receive the full advantages of current methods due to several restrictions, such as medication costs, accessibility, and concern about the adverse effects of drugs (Sasani et al., 2021). Due to the potentially severe complications of DM, recognizing new applicable approaches for prevention and controlling DM is critical. Identifying and utilizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…(M5). The results agreed with Lee et al, [33] who found, through a study conducted on humans suffering from high blood sugar, a role for spirulina in improving the health status of blood lipid profile, and the results agreed with Gargouri et al, [34] who found a role for spirulina algae supplements in lowering blood lipid profile of harmful cholesterol and improve the level of beneficial cholesterol in diabetic rats, the reason was explained by the ability of spirulina to reduce the absorption of cholesterol in the intestine, in addition to its content of the amino acid cysteine found in the protein C-Phycocyanins. On the other hand, the results were in line agreement with [35,36] how found through a study on humans how are suffering from diabetes type II how were supplemented with spirulina sauce every day as a treatment and they found a reduction in TG, TC and LDL when compared with their level in the beginning of the experiment and they observed reduction in waistline and hungriness and increase the feeling of fullness among patients.…”
Section: Effect On Blood Lipid Profile Parameterssupporting
confidence: 91%
“…(M5). The results agreed with Lee et al, [33] who found, through a study conducted on humans suffering from high blood sugar, a role for spirulina in improving the health status of blood lipid profile, and the results agreed with Gargouri et al, [34] who found a role for spirulina algae supplements in lowering blood lipid profile of harmful cholesterol and improve the level of beneficial cholesterol in diabetic rats, the reason was explained by the ability of spirulina to reduce the absorption of cholesterol in the intestine, in addition to its content of the amino acid cysteine found in the protein C-Phycocyanins. On the other hand, the results were in line agreement with [35,36] how found through a study on humans how are suffering from diabetes type II how were supplemented with spirulina sauce every day as a treatment and they found a reduction in TG, TC and LDL when compared with their level in the beginning of the experiment and they observed reduction in waistline and hungriness and increase the feeling of fullness among patients.…”
Section: Effect On Blood Lipid Profile Parameterssupporting
confidence: 91%
“…Echium plantagineum oil [ 237 ] and Quercus sp. fruits [ 238 ] have been shown to possess diverse antidiabetic and metabolic-syndrome-lowering activities by human clinical studies. Rosa rugosa [ 239 , 240 ] has also been reported, experimentally and ethnopharmacologically, to have such effects.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of diabetes-related enzymes was also confirmed by Nogueira et al [122], who obtained positive results of α-glucosidase inhibition via an acorn (Q. robur) buffer extract. Promising results related to the influence of acorn phenolic compounds on glycemic control were also obtained by Sasani et al [128], who conducted research based on the consumption of acorn muffins with acorn flour.…”
Section: Historical and Potential Modern Uses Of Acorns In Medicinementioning
confidence: 88%
“…The health-promoting properties of acorns are due to the presence of phytonutrients in them, among which the most important are phenolic compounds, triterpenes, sterols, tocopherols, and carotenoids [10,13]. Q. brantii extract from the seed hull with 70% ethanol mucoadhesive gel for the treatment of periodontitis antioxidant and antibacterial activity of polyphenols [125] water extract from acorns intraperitoneally administered at a single dose of 50 mg/kg-study on rats inhibition of hepatic enzymes (ALT, AST, ALP, and LDH)-prevents liver damage [121] hydroalcoholic extract from acorn internal fruit in vitro experiment inhibition of HEWL amyloid formation [127] acorn flour acorn muffins-oral administration in diet (10 g of acorn flour per day) reduction of glycated hemoglobin (HbA1c)-anti-diabetic activity of polyphenols [128] The high content of phenolic compounds is important for the health-promoting nature of acorns and products obtained from them. Şenol et al [123] and Gezici and Sekeroglu [131] indicated the relationship between the content of phenolic compounds in acorn extract and the inhibition of enzymes catalyzing the neurotransmitter degradation reaction: acetylcholinesterase (AChE) and butyrylcholinesterase (BChE).…”
Section: Historical and Potential Modern Uses Of Acorns In Medicinementioning
confidence: 99%